2014
DOI: 10.1016/j.jinorgbio.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-dependent bactericidal activities of Ag/CeO2 catalysts against Escherichia coli

Abstract: Silver-loaded CeO 2 nanomaterials (Ag/CeO 2 ) including Ag/CeO 2 nanorods, nanocubes, nanoparticles were prepared with hydrothermal and impregnation methods. Catalytic inactivation of Escherichia coli with Ag/CeO 2 catalysts through the formation of reactive oxygen species (ROS) was investigated. For comparison purposes, the bactericidal activities of CeO 2 nanorods, nanocubes and nanoparticles were also studied. There was a 3-4 log order improvement in the inactivation of E. coli with Ag/CeO 2 catalysts compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 40 publications
3
61
0
1
Order By: Relevance
“…5b) -formation on the surface of Ag/MnO 2 provided a strong indication that Ag/MnO 2 effectively activated the adsorbed oxygen to produce active oxygen species, which played important roles in the inactivation of E. coli. According to our results of U OH formation on the surface of Ag/CeO 2 (Wang et al, 2014) and Ag/MnO 2 in this study, it can be inferred that multivalent metal oxide supports are favorable to ROS formation.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…5b) -formation on the surface of Ag/MnO 2 provided a strong indication that Ag/MnO 2 effectively activated the adsorbed oxygen to produce active oxygen species, which played important roles in the inactivation of E. coli. According to our results of U OH formation on the surface of Ag/CeO 2 (Wang et al, 2014) and Ag/MnO 2 in this study, it can be inferred that multivalent metal oxide supports are favorable to ROS formation.…”
Section: Resultssupporting
confidence: 67%
“…Further, the interaction of Ag and the support can potentially promote the production of ROS and improve the bactericidal activity. Our previous studies showed that electron transfer between Ce 3+ /Ce , and the interaction of Ag and Ce was helpful for the production of ROS (Chang et al, 2008;Wang et al, 2014). In order to examine the universality of this concept, manganese oxides with variable valency were chosen for further research on bactericidal activity based on ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Other metal ions are also in ionic state as can be found from their binding energies compiled in Table 3. Noble metal ions dispersed on CeO 2 support reported by several research groups confirming ionic nature of noble metal ions in CeO 2 are also given in the table [89,99,[127][128][129][130][131][132][133][134][135][136].…”
Section: Electronic Structure Of Noble Metal Ion Substituted Ceo 2 Camentioning
confidence: 79%
“…According to the literature, cells incubation time at 37 °C in presence of DCFH-DA should range between 30 and 60 minutes, to permit the diffusion of probes inside cells and the hydrolysis by endogenous esterase3839. Nevertheless, these incubation times for samples containing solar irradiated E. coli may lead to modifications of physiological state of the cells, including ROS levels, due to metabolic activities during the incubation period.…”
Section: Resultsmentioning
confidence: 99%